Competitiveness of Indonesia’s Crude Palm Oil (CPO) in International Markets: Based on Database 2018 - Betrix Betrix; Halimah Cahyaning Fajri; Stanny Sicilia Rawung (Journal of International Conference Proceedings (JICP), 2022)
As one of the largest CPO exporting countries in the world, Indonesia has a CPO production that continues to increase every year. Through this study, an analysis of the factors affecting Indonesia's CPO competition in the international market in recent years was carried out. The growth of export volume has a positive and significant influence on the competitiveness of Indonesia’s CPO in the international market, while the selling price and inflation in the main export destination countries show a negative and significant influence on the competitiveness of Indonesia's CPO. Policy that can be taken to continue to be able to improve the competitiveness of Indonesia’s CPO by developing technology so that the quality and efficiency of Indonesia’s CPO production will increase. Increasing production efficiency accompanied by improving CPO quality has the opportunity to reduce Indonesia CPO price, thereby increasing export volumes and increasing the competitiveness of CPO itself. If the competitiveness of Indonesia CPO continues to increase, the world market tends to increase the demand for CPO imports from Indonesia, so that in the long run it has implications for the positiveness of Indonesia trade balance and increased growth Indonesia’s economy.Keywords: CPO, Data Panel, International Market, RCA